JAMU REINTERPRETATION AS CULTURAL HERITAGE THROUGH GASTRONOMY PRODUCTS AT HOTEL TENTREM JAKARTA - Valentine Shen Handoko; Andari Tirtadidjaja (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2026)
Jamu, a traditional Indonesian herbal preparation recognized by UNESCO in 2023 as Intangible Cultural Heritage, faces the challenge of remaining relevant amid modern consumer preferences. This study analyzes the forms of jamu reinterpretation as cultural heritage through gastronomy products at Hotel Tentrem Jakarta and examines how the cultural values of jamu are preserved throughout that process. A qualitative descriptive design was applied. Data were collected through semi-structured in-depth interviews with six purposively selected informants and complemented by field observation across four sessions and documentation. Analysis followed the Miles and Huberman model using Directed Content Analysis for data reduction, source triangulation for validity, and IFAS/EFAS matrices as supporting analytical tools. The findings show that Hotel Tentrem Jakarta reinterprets jamu into ten gastronomy products across pastry and beverage categories, employing modern techniques including foam, layering, infuse, sous vide, clarified, and churning while preserving the authentic flavor character and cultural identity of jamu. The reinterpretation is grounded in deep historical knowledge, authenticated ingredient use, and collaboration with traditional jamu experts. IFAS and EFAS average scores of 3.43 and 3.15 respectively indicate a strong strategic position. Consumer response is predominantly positive, though cultural narrative transmission to guests remains inconsistent and requires further systematization.